STABLE ISOTOPES IN CHAROPHYTE INCRUSTATIONS: RELATIONSHIPS WITH CLIMATE AND WATER CHEMISTRY - Coletta P.; Pentecost A.; Spiro B. (My University, 2001)
Age gradients of stable C and O isotopes were found in modern Chara hispida calcite incrustations allowing seasonal changes in water chemistry to be observed. Gradients resulted from apical calcification in growing charophytes. In a regional study of 12 species and varieties of charophytes the carbonate δ13C differed significantly with 'low value' and 'high value' species such as Chara globularis and C. baltica, respectively. Samples from lakes and other stagnant waters had significantly higher δ13C values than those sampled from flowing water. The differences were related mainly to photosynthesis.Charophyte δ18O (carbonate) was not significantly different between species but water chemistry was important for brackish water Lamprothamnium papulosum. The overall δ18O (carbonate) was positively correlated with groundwater δ18O and it is suggested that more reliable environmental information is available from δ18O than δ13C in charophyte marls. The mean charophyte carbonate δ13C and δ18O was -5.7%% and -6.4%% VPDB, respectively. Environmental temperature estimates suggested that at some sites the carbonate was deposited close to isotopic equilibrium, but in others a slight to moderate disequilibrium was indicated.
Keywords: CHAROPHYTES; CARBON; OXYGEN; STABLE; ISOTOPES; MARL